Invariant and variable intermolecular interactions in functionalized malonic acid half-esters: X-ray, Hirshfeld surface and PIXEL energy analyses. Issue 4 (5th December 2014) - Venkatesan, Perumal; Thamotharan, Subbiah; Kumar, Rajendran Ganesh; Ilangovan, Andivelu
Abstract : A series of functionalized malonic acid half-ester derivatives have been synthesized and their crystal structures are determined. Invariant and variable intermolecular interactions in these derivatives are analysed using Hirshfeld surfaces and PIXEL energy calculations. Abstract : A series of functionalized malonic acid half-ester derivatives (parent compoundMHE-1 ), with variations in functional groups at different positions on the aromatic ring, have been synthesized and crystal structures are determined at room temperature (296 K). The methyl (4-CH3, MHE-2 ) and chloro (4-Cl, MHE-3 ) derivatives are isomorphous with each other. The overall crystal packing ofMHE-1–3 is similar. However, there are few differences observed between stacking of layers in these structures. Compounds with nitro (3-NO2, MHE-4 ) and ethyl ester (2-COOC2 H5, MHE-5 ) substituents crystallize in different space groups and thus crystal packing is different when compared toMHE-1–3 . In all the structures, intramolecular N–H⋯O and O–H⋯O hydrogen bonds generate a two fused S (6) ring motif. A detailed study is carried out to visualize intermolecular interactions observed in all five crystal structures (MHE-1–5 ) using Hirshfeld surface (HS) analysis with two dimensional fingerprint plots. The relative contribution of intermolecular H⋯H contacts inMHE-3 is substantially lower than that inMHE-1–2, though similar crystal packing arrangements ofMHE-1–3 andMHE-2 andMHE-3 are isomorphous. From HS analysis it is clear that the observed H⋯H contact contribution (MHE-3 ) is a consequence of the presence of the chlorine substituent and growing contribution of Cl⋯H contacts. The relative contributions of other intermolecular contacts involving various atoms are comparable inMHE-1–3 structures. The intermolecular interaction energies are quantified using PIXEL for various molecular pairs extracted from respective crystal structures. Interestingly, there are some invariant and variable intermolecular contacts observed between different groups in all five structures.